Solid electrolytic capacitor and hybrid electrolytic capacitor

By using solid electrolytes composed of conductive polymers and zwitterionic compounds in electrolytic capacitors or mixed electrolytes, the problem of high capacitance decay rate and ESR resistance increase rate at low temperatures is solved, and better low-temperature performance is achieved.

CN119581228APending Publication Date: 2025-03-07SYNMAX BIOCHEM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411248239.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-06
Filing Date
2024-09-06
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The existing electrolytic capacitors have high capacitance decay rate and ESR resistance increase rate at low temperatures, and novel electrolyte composition is needed to overcome this problem.

Method used

A solid electrolyte including a conductive polymer and a zwitterionic compound is used, or a zwitterionic compound is added to the solid electrolyte and liquid electrolyte to form a dielectric oxide film surface on the anode foil. The chemical structure of the zwitterionic compound is a linear or branched alkyl group of R1-6, R2, R3, and R4 are each independently a linear or branched alkyl group of H or C1-6; and a linear or branched alkyl group of L is a linear or branched alkyl group of C1-12.

Benefits of technology

It significantly reduces the capacitance decay rate and ESR resistance increase rate at low temperatures, and improves the performance of electrolytic capacitors in low temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581228A_ABST
    Figure CN119581228A_ABST
Patent Text Reader

Abstract

A solid electrolytic capacitor and a hybrid electrolytic capacitor. A hybrid electrolytic capacitor includes an anode foil having a dielectric oxide film thereon; a cathode foil; the isolating membrane is positioned between the anode foil and the cathode foil; the solid electrolyte is formed on the surface of the dielectric oxide film of the anode foil, and the solid electrolyte comprises a conductive polymer; and the liquid electrolyte is filled in the space among the anode foil, the cathode foil and the isolating membrane, and the liquid electrolyte comprises a solvent with the boiling point higher than 150 DEG C. Solid electrolyte, liquid electrolyte, or both comprising zwitterionic compounds having a chemical structure # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] Embodiments of the present invention relate to electrolytic capacitors, and more particularly to the composition of electrolytes thereof. Background Art

[0002] Electrolytic capacitors are usually made of porous dielectrics formed by oxidation of the metal surface, and liquid or solid conductive materials are introduced into this porous structure to form cathodes and anodes. Commonly used aluminum capacitors are made by winding or stacking, and other electrical connectors and packaging are used on the outside to obtain electrolytic capacitors.

[0003] The low-temperature capacitance decay rate and low-temperature ESR resistance increase rate of current electrolytic capacitors at low temperatures are relatively high, so novel electrolyte compositions are urgently needed to overcome the above problems. Summary of the invention

[0004] A solid electrolytic capacitor provided by one embodiment of the present invention comprises: an anode foil having a dielectric oxide film thereon; a cathode foil; a separator located between the anode foil and the cathode foil; and a solid electrolyte formed on the surface of the dielectric oxide film on the anode foil; wherein the solid electrolyte comprises a conductive polymer and a zwitterionic compound, wherein the chemical structure of the zwitterionic compound is Where R 1 It is C 1-6 A straight or branched alkyl group; R 2 , R 3 , and R 4 Each is independently H or C 1-6 A linear or branched alkyl group; and L is C 1-12 A straight chain or branched alkylene group.

[0005] In some embodiments, the zwitterionic compound comprises 1 wt % to 50 wt % of the solid electrolyte.

[0006] In some embodiments, the conductive polymer includes poly (3,4-dioxyethylthiophene: polystyrene sulfonic acid) (PEDOT:PSS), poly (thiophene), poly (p-phenylene sulfide), polycarbazole, polyindole, polyaniline, polypyrrole, poly (fluorene), polyphenylene, polypyrene, polyazulene, polynaphthalene, polyacetylene, or poly (p-phenylenevinylene).

[0007] The hybrid electrolytic capacitor provided by the embodiment of the present invention comprises: an anode foil having a dielectric oxide film thereon; a cathode foil; a separator located between the anode foil and the cathode foil; a solid electrolyte formed on the surface of the dielectric oxide film on the anode foil, and the solid electrolyte comprises a conductive polymer; and a liquid electrolyte filled in the space between the anode foil, the cathode foil, and the separator, and the liquid electrolyte comprises a solvent having a boiling point higher than 150° C., wherein the solid electrolyte, the liquid electrolyte, or both of the above comprises a zwitterionic compound, and its chemical structure is Where R 1 It is C 1-6 A straight or branched alkyl group; R 2 , R 3 , and R 4 Each is independently H or C 1-6 A linear or branched alkyl group; and L is C 1-12 A straight chain or branched alkylene group.

[0008] In some embodiments, when the solid electrolyte includes the zwitterionic compound, the zwitterionic compound accounts for 1 wt % to 50 wt % of the solid electrolyte.

[0009] In some embodiments, when the liquid electrolyte includes a zwitterionic compound, the zwitterionic compound accounts for 1 wt % to 50 wt % of the liquid electrolyte.

[0010] In some embodiments, when the solid electrolyte and the liquid electrolyte include zwitterionic compounds, the chemical structure of the zwitterionic compound in the solid electrolyte is the same as the chemical structure of the zwitterionic compound in the liquid electrolyte.

[0011] In some embodiments, when the solid electrolyte and the liquid electrolyte include zwitterionic compounds, the chemical structure of the zwitterionic compound in the solid electrolyte is different from the chemical structure of the zwitterionic compound in the liquid electrolyte.

[0012] In some embodiments, the solvent having a boiling point higher than 150° C. includes propylene glycol, glycerol, γ-butyrolactone, γ-valerolactone, N-methylpyrrolidone, dimethyl sulfoxide, or sulfolane.

[0013] In some embodiments, the liquid electrolyte further comprises a liquid polymer.

[0014] In some embodiments, the liquid polymer comprises a polyalkylene glycol. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 is a schematic diagram of a wound blank electrode body in one embodiment of the present invention;

[0016] Figure 2Ais a schematic diagram of an electrode body and a solid electrolyte in one embodiment of the present invention;

[0017] Figure 2B is a schematic diagram of an electrode body and a mixed electrolyte in one embodiment of the present invention;

[0018] Figure 3 FIG. 1 is a schematic diagram of an electrolytic capacitor in one embodiment of the present invention.

[0019]

Explanation of symbols

[0020] 100: Wound blank electrode body

[0021] 101: Anode foil

[0022] 102: Isolation film

[0023] 103: Cathode foil

[0024] 104: Anode wire

[0025] 105: cathode wire

[0026] 200:Mixed electrolyte

[0027] 201: Dielectric oxide film

[0028] 202: Solid electrolyte

[0029] 203:Liquid Electrolyte

[0030] 300: Encapsulation

[0031] 301: Shell

[0032] 302: Capping

[0033] 303: Packaging glue DETAILED DESCRIPTION

[0034] In one embodiment of the present invention, a capacitor is prepared using a wound blank electrode body. Figure 1As shown, the anode foil 101 and cathode foil 103 contained in the wound blank electrode body 100 are metal foils, and the anode foil 101 further has a dielectric oxide film 201 such as a porous metal oxide thereon. The separator 102 is sandwiched between the anode foil 101 and the cathode foil 103. The anode foil 101 and the cathode foil 103 can each be beryllium, magnesium, aluminum, germanium, tin, antimony, bismuth, titanium, zirconium, hafnium, vanadium, niobium, tantalum, tungsten, or an alloy thereof. The dielectric oxide film 201 such as a porous metal oxide can be a porous oxide of the metal corresponding to the anode foil 101. For example, the anode foil 101 can be an aluminum foil, and the dielectric oxide film 201 can be a porous aluminum oxide. The separator 102 can be cellulose, polyethylene terephthalate, polybutylene terephthalate, polyethylene, polypropylene, polyvinylidene fluoride, other suitable polymers, blends thereof, or multilayer structures thereof. The anode foil 101 , the cathode foil 103 , and the separator 102 are wound into a roll, and the anode lead 104 and the cathode lead 105 are connected to the anode foil 101 and the cathode foil 103 , respectively, to form a wound blank electrode body 100 .

[0035] like Figure 2A As shown, a solid electrolyte 202 can be formed on the surface of the dielectric oxide film 201 on the anode foil 101 in the wound blank electrode body 100. The method for forming the solid electrolyte 202 can be to immerse the wound blank electrode body 100 in a dispersion containing a solid electrolyte, repeatedly draw and release the vacuum for multiple times so that the surface of the dielectric oxide film 201 on the anode foil 101 of the wound blank electrode body 100 absorbs the dispersion containing the solid electrolyte and then dries. Repeat the adsorption and drying steps multiple times to form the solid electrolyte 202 on the surface of the dielectric oxide film 201 on the anode foil 101.

[0036] like Figure 3 As shown, the wound blank electrode body 100 with the solid electrolyte 202 is placed in a housing 301. The housing 301 is covered with a cover 302, and then the housing 301, the cover 302, the gap between the anode lead 104 and the cathode lead 105 are sealed with a packaging glue 303 to form a package 300, that is, a solid electrolytic capacitor (containing only the solid electrolyte 202 without a liquid electrolyte) is formed.

[0037] On the other hand, a solid electrolyte 202 is formed on the surface of the dielectric oxide film 201 on the anode foil 101 in the wound blank electrode body 100. The formation method is as described above and will not be repeated here. Then, the wound blank electrode body 100 with the solid electrolyte 202 is immersed in the liquid electrolyte 203, and the vacuum is repeatedly drawn and released for multiple times to facilitate the electrode body to absorb the liquid electrolyte 203. The combination of the liquid electrolyte 203 and the solid electrolyte 202 is the hybrid electrolyte 200. After the wound blank electrode body 100 with the hybrid electrolyte 200 is placed in the housing 301, the housing 301 is covered with a cover 302, and then the housing 301, the cover 302, the gap between the anode wire 104, and the cathode wire 105 are sealed with a packaging glue 303 to form a package 300, that is, a hybrid electrolytic capacitor (containing a solid electrolyte 202 and a liquid electrolyte 203) is formed.

[0038] In one embodiment, the solid electrolytic capacitor includes an anode foil 101 (having a dielectric oxide film 201 thereon), a cathode foil 103, and a separator 102 located between the anode foil 101 and the cathode foil 103. Figure 2A The solid electrolyte 202 is formed on the surface of the dielectric oxide film 201 on the anode foil 101, and the solid electrolyte 202 includes a conductive polymer and a zwitterionic compound, wherein the chemical structure of the zwitterionic compound is R 1 It is C 1-6 A straight chain or branched alkyl group, R 2 , R 3 , and R 4 Each is independently H or C 1-6 A linear or branched alkyl group; and L is C 1-12 A straight chain or branched alkylene group.

[0039] In some embodiments, the zwitterionic compound accounts for 1 wt % to 50 wt % of the solid electrolyte 202. If the ratio of the zwitterionic compound is too low, the effect is similar to that of no zwitterionic compound; if the ratio of the zwitterionic compound is too high, it is not conducive to the matrix properties of the conductive polymer. In some embodiments, the conductive polymer includes poly (3,4-dioxyethylthiophene: polystyrene sulfonic acid) (PEDOT:PSS), poly (thiophene), poly (p-phenylenesulfide), polycarbazole, polyindole, polyaniline, polypyrrole, poly (fluorene), polyphenylene, polypyrene, polyazulene, polynaphthalene, polyacetylene, or poly (p-phenylene vinylene).

[0040] The hybrid electrolytic capacitor provided by one embodiment of the present invention includes an anode foil 101 (having a dielectric oxide film 201 thereon), a cathode foil 103, and a separator 102 located between the anode foil 101 and the cathode foil 103. Figure 2B As shown. The solid electrolyte 202 is formed on the surface of the dielectric oxide film 201 on the anode foil 101, and the solid electrolyte 202 includes a conductive polymer. The types of conductive polymers are as described above and are not repeated here. The liquid electrolyte 203 fills the space between the anode foil, the cathode foil, and the separator, and the liquid electrolyte 203 includes a solvent with a boiling point higher than 150°C.

[0041] In the hybrid electrolytic capacitor, the solid electrolyte 202, the liquid electrolyte 203, or both of them include zwitterionic compounds, the chemical structure of which is R 1 It is C 1-6 A straight or branched alkyl group; R 2 , R 3 , and R 4 Each is independently H or C 1-6 A linear or branched alkyl group; and L is C 1-12 A straight chain or branched alkylene group.

[0042] In some embodiments, when the solid electrolyte 202 includes the zwitterionic compound, the zwitterionic compound accounts for 1 wt% to 50 wt% of the solid electrolyte. If the proportion of the zwitterionic compound is too low, the effect is similar to that without the zwitterionic compound; if the proportion of the zwitterionic compound is too high, it is not conducive to the matrix properties of the conductive polymer. In some embodiments, when the liquid electrolyte 203 includes the zwitterionic compound, the zwitterionic compound accounts for 1 wt% to 50 wt% of the liquid electrolyte. If the proportion of the zwitterionic compound is too low, the effect is similar to that without the zwitterionic compound. If the proportion of the zwitterionic compound is too high, the viscosity will be too thick and not conducive to filling and adsorption. The most appropriate proportion is between 10 wt% and 30 wt%.

[0043] In some embodiments, when the solid electrolyte 202 and the liquid electrolyte 203 include zwitterionic compounds, the chemical structure of the zwitterionic compound in the solid electrolyte 202 is the same as the chemical structure of the zwitterionic compound in the liquid electrolyte 203 .

[0044] In some embodiments, when the solid electrolyte 202 and the liquid electrolyte 203 include zwitterionic compounds, the chemical structure of the zwitterionic compound in the solid electrolyte 202 is different from the chemical structure of the zwitterionic compound in the liquid electrolyte 203 .

[0045] In some embodiments, solvents having a boiling point higher than 150°C include propylene glycol, glycerol, γ-butyrolactone, γ-valerolactone, N-methylpyrrolidone, dimethyl sulfoxide or cyclobutane sulfone. If the boiling point of the solvent is lower than or equal to 150°C, it is easy to explode when exposed to high temperature, and the electrolyte scatters and causes a short circuit. For safety reasons, in some embodiments, the liquid electrolyte also includes a liquid polymer such as polyalkylene glycol, which helps to increase the stability of the liquid electrolyte. In some embodiments, the polyalkylene glycol may be polyethylene glycol. In some embodiments, the molecular weight of the polyalkylene glycol may be 200 to 2000. If the molecular weight of the polyalkylene glycol is too low, the boiling point is too low and does not meet the requirements. If the molecular weight of the alkylene glycol is too high, it may be solid rather than liquid.

[0046] It should be noted that the above-mentioned method for forming the capacitor is only used as an example and is not intended to limit the present invention. A person skilled in the art can use any method to form the capacitor of the present invention, and is not limited to the above-mentioned method.

[0047] In addition, the formation method of the zwitterionic compound can be to react an imidazole compound with a sultone compound as follows. It is understood that the following method for synthesizing zwitterionic compounds is only used as an example and is not intended to limit the present invention. A person with ordinary knowledge in the art can synthesize zwitterionic compounds by any method, and is not limited to the following synthesis method.

[0048]

[0049] In some embodiments, the chemical structure of the zwitterionic compound formed by the above reaction can be

[0050]

[0051]

[0052] or other suitable chemical structures.

[0053] It is known from experiments that solid electrolytic capacitors or hybrid electrolytic capacitors using zwitterionic compounds have lower low-temperature capacitance decay rate and low-temperature ESR resistance increase rate.

[0054] In order to make the above contents and other purposes, features, and advantages of the present disclosure more clearly understood, embodiments are given below and described in detail with reference to the accompanying drawings:

[0055] [Example]

[0056] In the following embodiments, a wound blank electrode body (CHINSAN electronic) is used. The wound blank electrode body contains an anode foil which is an aluminum foil with a surface oxidized to porous aluminum oxide (such as a dielectric oxide film), a cathode foil which is an aluminum foil with a smooth surface, and a separator sandwiched between the anode foil and the cathode foil. The anode foil, the cathode foil, and the separator are wound into a roll, and the anode wire and the cathode wire are connected to the anode foil and the cathode foil respectively to form a wound blank electrode body.

[0057] The wound blank electrode body is immersed in the dispersion liquid, and the vacuum is repeatedly drawn and released for multiple times to promote adsorption. Then, the wound blank electrode body adsorbed with the dispersion liquid is dried at high temperature for a period of time. The adsorption and drying steps are repeated three times to form a solid electrolyte on the surface of the dielectric oxide film on the anode foil. The wound blank electrode body with the solid electrolyte is placed in a shell. The shell is covered with a cover, and then the gap between the shell, the cover, the anode wire, and the cathode wire is sealed with a packaging glue to form a solid electrolytic capacitor (containing only solid electrolyte and no liquid electrolyte).

[0058] On the other hand, after forming a solid electrolyte on the surface of the porous aluminum oxide (such as a dielectric oxide film) on the anode foil, the wound blank electrode body with the solid electrolyte is immersed in the liquid electrolyte, and the vacuum is repeatedly drawn and released multiple times to facilitate the electrode body to absorb the liquid electrolyte. The combination of the liquid electrolyte and the solid electrolyte is a hybrid electrolyte. After the wound blank electrode body with the hybrid electrolyte is placed in a shell, the shell is covered with a cover, and then the shell, the cover, the anode wire, and the gap between the cathode wire are sealed with a packaging glue, so as to form a hybrid electrolytic capacitor (containing a solid electrolyte and a liquid electrolyte).

[0059] In the following examples, the viscosity of the dispersion or liquid electrolyte was measured using a rheometer (Brookfield LVDV-II pro) at a shear rate of 100 Hz at 25°C.

[0060] In the following examples, the dispersion (2.5 g) was dried at 130° C. for 3 hours and the solid content of the dispersion was determined by differential gravimetric method.

[0061] In the following examples, an LCR meter (Agilent 4263B) was used to measure the capacitance of capacitors at room temperature, -40°C, and -55°C at 35V at 120Hz to calculate the low temperature capacitance decay rate (%) of the capacitor at low temperature compared to the capacitor at room temperature.

[0062] In the following embodiments, an LCR meter (Agilent 4263B) was used to measure the equivalent series resistance (ESR) of capacitors at room temperature, -40°C, and -55°C at 35V at 100KHz to calculate the low temperature ESR resistance increase rate (%) of the capacitor at low temperature compared to the capacitor at room temperature.

[0063] Synthesis Example 1 (Compound I-1)

[0064] 1-Methylimidazole (24.6 g, 0.3 mol) was dissolved in ethylene glycol dimethyl ether (100 g), and the temperature was raised to 80°C under a nitrogen system. 1,4-Butane sultone (40.8 g, 0.3 mol) was gradually dropped into the solution within 1 hour, and then maintained at 80°C for 3 hours, and then cooled to 0°C to 5°C to precipitate a white solid. The solid was collected after filtration and dried under vacuum to obtain compound I-1 (43.2 g), which appeared as white crystals. The hydrogen spectrum of compound I-1 is as follows: 1 H-NMR (500MHz, CD 3OD): 1.78-1.84 (m, 2H), 2.04-2.10 (m, 2H), 2.87 (t, 2H, J = 7.5 Hz), 3.96 (s, 3H), 4.29 (t, 2H, J = 7.3 Hz), 7.59 (d, 1H, J = 2.5 Hz), 7.68 (d, 1H, J = 2.5 Hz), 8.99 (s, 1H). The carbon spectrum of compound I-1 is as follows: 13 C-NMR (125MHz, CD 3 OD):22.88,30.00,36.69,50.44,51.61,123.83,125.13,138.12. The above reaction is shown in the following formula:

[0065]

[0066] Synthesis Example 2 (Compound I-2)

[0067] 1,2-dimethylimidazole (28.8 g, 0.3 mol) was dissolved in ethylene glycol dimethyl ether (100 g), and the temperature was raised to 80°C under a nitrogen system. 1,4-Butane sultone (40.8 g, 0.3 mol) was gradually dropped into the solution within 1 hour, and then maintained at 80°C for 3 hours, and then cooled to 0°C to 5°C to precipitate a white solid. The solid was collected after filtration and dried under vacuum to obtain compound I-2 (60.2 g), which appeared as white crystals. The hydrogen spectrum of compound I-2 is as follows: 1 H-NMR (500MHz, CD 3 OD): 1.82-1.88 (m, 2H), 2.02-2.08 (m, 2H), 2.70 (s, 3H), 2.89 (t, 2H, J = 7.3 Hz), 3.87 (s, 3H), 4.25 (t, 2H, J = 7.50 Hz), 7.52 (d, 1H, J = 2.0 Hz), 7.59 (d, 1H, J = 2.0 Hz). The carbon spectrum of compound I-2 is as follows: 13 C-NMR (125MHz, CD 3 OD):9.67,22.99,29.59,35.54,51.58,122.38,123.78,146.12. The above reaction is shown in the following formula:

[0068]

[0069] Preparation Example 1 (Liquid Electrolyte H-1)

[0070] Propylene glycol (50 g) and compound I-1 (25 g) were mixed and heated to dissolve, and then liquid polymer PEG-400 (25 g) was added. After stirring and cooling to room temperature, liquid electrolyte H-1 was obtained.

[0071] Preparation Example 2 (Liquid Electrolyte H-2)

[0072] Propylene glycol (85 g) and compound I-2 (15 g) were mixed and heated to dissolve, and then stirred and cooled to room temperature to obtain liquid electrolyte H-2.

[0073] Preparation Example 3 (Liquid Electrolyte H-3)

[0074] Propylene glycol (60 g) and liquid polymer PEG-400 (30 g) were mixed and heated to dissolve, stirred and cooled to room temperature to obtain liquid electrolyte H-3.

[0075] Preparation Example 4 (Dispersion D-1, without zwitterionic compound)

[0076] A liquid containing 1.3% PEDOT / PSS (85 g, CP-WL2A purchased from Dali Polymer, pH = 4.0) and a mixed liquid (15 g, a weight ratio of propylene glycol: glycerol: PEG-400 of 1:2:2) were vigorously stirred to obtain a dispersion D-1.

[0077] Preparation Example 5 (Dispersion D-2, containing compound I-1)

[0078] A liquid containing 1.3% PEDOT / PSS (85 g, CP-WL2A purchased from Dali Polymer, pH = 4.0), a mixed liquid (14 g, a weight ratio of propylene glycol: glycerol: PEG-400 of 1:2:2), and compound I-1 (1 g) were vigorously stirred to obtain a dispersion D-2.

[0079] The properties of the above liquid electrolyte and dispersion are shown in Table 1:

[0080] Table 1

[0081] pH Solid content (%) Viscosity(cP) Liquid Electrolyte H-1 - - 54.5 Liquid Electrolyte H-2 - - 47.5 Liquid Electrolyte H-3 - - 43.9 Dispersion D-1 3.09 9.13 13.0 Dispersion D-2 3.08 9.74 12.9

[0082] The pH of dispersions D-1 and D-2 was maintained between 3 and 4, the solid content was maintained between 9% and 10%, and the viscosity was maintained at a low level (<15cP). The viscosity of the liquid electrolyte was maintained below 60cP, and the adsorption was good during the subsequent immersion of the wound blank electrode body.

[0083] Example 1 (Solid Electrolytic Capacitor)

[0084] Immerse the wound blank electrode body in dispersion D-2, and repeatedly evacuate and release the vacuum for 8 times to promote adsorption. Then dry the wound blank electrode body after adsorbing dispersion D-2 at 135°C for 30 minutes. Repeat the adsorption and drying steps 3 times to form a solid electrolyte on the surface of the porous alumina (such as a dielectric oxide film) on the anode foil. Place the wound blank electrode body with the solid electrolyte into a casing. Cover the casing with a cover, and then seal the gap between the casing, the cover, the anode wire, and the cathode wire with packaging glue to form a solid electrolytic capacitor. Measure the capacitance and ESR of this capacitor at different temperatures to calculate its capacitance decay rate and ESR resistance increase rate at different temperatures.

[0085] Example 2 (Hybrid Electrolytic Capacitor)

[0086] The wound blank electrode body is immersed in the dispersion D-1, and the vacuum is repeatedly drawn and released 8 times to promote adsorption. Then, the wound blank electrode body after adsorbing the dispersion D-1 is dried at 135°C for 30 minutes. The adsorption and drying steps are repeated 3 times to form a solid electrolyte on the surface of the porous alumina (such as a dielectric oxide film) on the anode foil. The wound blank electrode body with the solid electrolyte is immersed in the liquid electrolyte H-1, and the vacuum is repeatedly drawn and released 8 times to facilitate the electrode body to adsorb the liquid electrolyte H-1. The combination of liquid electrolyte H-1 and solid electrolyte is a hybrid electrolyte. After the wound blank electrode body with the hybrid electrolyte is placed in a casing, the casing is covered with a cover, and then the casing, the cover, the gap between the anode wire and the cathode wire are sealed with packaging glue to form a hybrid electrolytic capacitor. The capacitance and ESR of this capacitor at different temperatures are measured to calculate its capacitance decay rate and ESR resistance increase rate at different temperatures.

[0087] Example 3 (Hybrid Electrolytic Capacitor)

[0088] The wound blank electrode body is immersed in the dispersion D-2, and the vacuum is repeatedly drawn and released 8 times to promote adsorption. Then, the wound blank electrode body after adsorbing the dispersion D-2 is dried at 135°C for 30 minutes. The adsorption and drying steps are repeated 3 times to form a solid electrolyte on the surface of the porous alumina (such as a dielectric oxide film) on the anode foil. The wound blank electrode body with the solid electrolyte is immersed in the liquid electrolyte H-1, and the vacuum is repeatedly drawn and released 8 times to facilitate the electrode body to adsorb the liquid electrolyte H-1. The combination of liquid electrolyte H-1 and solid electrolyte is a hybrid electrolyte. After the wound blank electrode body with the hybrid electrolyte is placed in a casing, the casing is covered with a cover, and then the casing, the cover, the gap between the anode wire and the cathode wire are sealed with packaging glue to form a hybrid electrolytic capacitor. The capacitance and ESR of this capacitor at different temperatures are measured to calculate its capacitance decay rate and ESR resistance increase rate at different temperatures.

[0089] Example 4 (Hybrid Electrolytic Capacitor)

[0090] The wound blank electrode body is immersed in the dispersion D-1, and the vacuum is repeatedly drawn and released 8 times to promote adsorption. Then, the wound blank electrode body after adsorbing the dispersion D-1 is dried at 135°C for 30 minutes. The adsorption and drying steps are repeated 3 times to form a solid electrolyte on the surface of the porous alumina (such as a dielectric oxide film) on the anode foil. The wound blank electrode body with the solid electrolyte is immersed in the liquid electrolyte H-2, and the vacuum is repeatedly drawn and released 8 times to facilitate the electrode body to adsorb the liquid electrolyte H-2. The combination of liquid electrolyte H-2 and solid electrolyte is a hybrid electrolyte. After the wound blank electrode body with the hybrid electrolyte is placed in a casing, the casing is covered with a cover, and then the casing, the cover, the gap between the anode wire and the cathode wire are sealed with packaging glue to form a hybrid electrolytic capacitor. The capacitance and ESR of this capacitor at different temperatures are measured to calculate its capacitance decay rate and ESR resistance increase rate at different temperatures.

[0091] Example 5 (Hybrid Electrolytic Capacitor)

[0092] The wound blank electrode body is immersed in the dispersion D-2, and the vacuum is repeatedly drawn and released 8 times to promote adsorption. Then, the wound blank electrode body after adsorbing the dispersion D-2 is dried at 135°C for 30 minutes. The adsorption and drying steps are repeated 3 times to form a solid electrolyte on the surface of the porous alumina (such as a dielectric oxide film) on the anode foil. The wound blank electrode body with the solid electrolyte is immersed in the liquid electrolyte H-2, and the vacuum is repeatedly drawn and released 8 times to facilitate the electrode body to adsorb the liquid electrolyte H-2. The combination of liquid electrolyte H-2 and solid electrolyte is a hybrid electrolyte. After the wound blank electrode body with the hybrid electrolyte is placed in a casing, the casing is covered with a cover, and then the casing, the cover, the gap between the anode wire and the cathode wire are sealed with packaging glue to form a hybrid electrolytic capacitor. The capacitance and ESR of this capacitor at different temperatures are measured to calculate its capacitance decay rate and ESR resistance increase rate at different temperatures.

[0093] Example 6 (Hybrid Electrolytic Capacitor)

[0094] The wound blank electrode body is immersed in the dispersion D-2, and the vacuum is repeatedly drawn and released 8 times to promote adsorption. Then, the wound blank electrode body after adsorbing the dispersion D-2 is dried at 135°C for 30 minutes. The adsorption and drying steps are repeated 3 times to form a solid electrolyte on the surface of the porous alumina (such as a dielectric oxide film) on the anode foil. The wound blank electrode body with the solid electrolyte is immersed in the liquid electrolyte H-3, and the vacuum is repeatedly drawn and released 8 times to facilitate the electrode body to adsorb the liquid electrolyte H-3. The combination of liquid electrolyte H-3 and solid electrolyte is a hybrid electrolyte. After the wound blank electrode body with the hybrid electrolyte is placed in a casing, the casing is covered with a cover, and then the casing, the cover, the gap between the anode wire and the cathode wire are sealed with packaging glue to form a hybrid electrolytic capacitor. The capacitance and ESR of this capacitor at different temperatures are measured to calculate its capacitance decay rate and ESR resistance increase rate at different temperatures.

[0095] Comparative Example 1 (Solid Electrolytic Capacitor)

[0096] Immerse the wound blank electrode body in dispersion D-1, and repeatedly evacuate and release the vacuum for 8 times to promote adsorption. Then dry the wound blank electrode body after adsorbing dispersion D-1 at 135°C for 30 minutes. Repeat the adsorption and drying steps 3 times to form a solid electrolyte on the surface of the porous alumina (such as a dielectric oxide film) on the anode foil. Place the wound blank electrode body with the solid electrolyte into a casing. Cover the casing with a cover, and then seal the gap between the casing, the cover, the anode wire, and the cathode wire with packaging glue to form a solid electrolytic capacitor. Measure the capacitance and ESR of this capacitor at different temperatures to calculate its capacitance decay rate and ESR resistance increase rate at different temperatures.

[0097] Comparative Example 2 (Hybrid Electrolytic Capacitor)

[0098] The wound blank electrode body is immersed in the dispersion D-1, and the vacuum is repeatedly drawn and released 8 times to promote adsorption. Then, the wound blank electrode body after adsorbing the dispersion D-1 is dried at 135°C for 30 minutes. The adsorption and drying steps are repeated 3 times to form a solid electrolyte on the surface of the porous alumina (such as a dielectric oxide film) on the anode foil. The wound blank electrode body with the solid electrolyte is immersed in the liquid electrolyte H-3, and the vacuum is repeatedly drawn and released 8 times to facilitate the electrode body to adsorb the liquid electrolyte H-3. The combination of liquid electrolyte H-3 and solid electrolyte is a hybrid electrolyte. After the wound blank electrode body with the hybrid electrolyte is placed in a casing, the casing is covered with a cover, and then the casing, the cover, the gap between the anode wire and the cathode wire are sealed with packaging glue to form a hybrid electrolytic capacitor. The capacitance and ESR of this capacitor at different temperatures are measured to calculate its capacitance decay rate and ESR resistance increase rate at different temperatures.

[0099] The composition of the above capacitors and the capacitance decay rate at different temperatures (compared to the capacitance at room temperature) are shown in Table 2:

[0100] Table 2

[0101]

[0102]

[0103] Table 2 shows that Example 1, which contains a solid electrolyte of Compound I-1, has a lower low-temperature capacitance decay rate (δCap) of a solid electrolytic capacitor than Comparative Example 1, indicating that zwitterionic compounds such as Compound I-1 can improve the low-temperature capacitance decay problem. The hybrid electrolytic capacitor of Comparative Example 2 has a good low-temperature capacitance decay rate (-13.6%) at -40°C, but a poor low-temperature capacitance decay rate (-20.8%) at a more severe low temperature such as -55°C. In addition to having a good low-temperature capacitance decay rate (best -11.8%) at -40°C, the hybrid electrolytic capacitors of Examples 2 to 6 of the present invention have a low-temperature capacitance decay rate (best -16.2%) at a more severe low temperature such as -55°C that is better than Comparative Example 2. From the above, it can be seen that adding zwitterionic compounds (such as Compound I-1 or I-2) to solid electrolytes, liquid electrolytes, or both can reduce the low-temperature capacitance decay rate of hybrid electrolytic capacitors.

[0104] Table 3

[0105]

[0106]

[0107] As shown in Table 3, the solid electrolytic capacitor or hybrid electrolytic capacitor using zwitterionic compounds in the embodiments of the present invention has a lower ESR resistance increase rate at the harsh temperature of -55°C than that of the comparative example. The above experiments prove that the electrolytic capacitor using zwitterionic compounds has a lower low-temperature ESR resistance increase rate.

[0108] Although the present disclosure has been disclosed as above with several preferred embodiments, they are not intended to limit the present disclosure. Any person with ordinary knowledge in the technical field can make any changes and modifications without departing from the spirit and scope of the present disclosure. Therefore, the protection scope of the present disclosure shall be based on the definition of the attached patent application scope.

Claims

1. A solid electrolytic capacitor, characterized in that: include: an anode foil having a dielectric oxide film thereon; a cathode foil; a separator disposed between the anode foil and the cathode foil; as well as a solid electrolyte formed on the surface of the dielectric oxide film on the anode foil; The solid electrolyte includes a conductive polymer and a zwitterionic compound, wherein the chemical structure of the zwitterionic compound is Where R 1 It is C 1-6 A straight or branched alkyl group; R 2 , R 3 , and R 4 Each is independently H or C 1-6 A straight or branched alkyl group; and L is C 1-12 A straight chain or branched alkylene group.

2. The solid electrolytic capacitor according to claim 1, characterized in that The zwitterionic compound accounts for 1 wt % to 50 wt % of the solid electrolyte.

3. The solid electrolytic capacitor according to claim 1, characterized in that: The conductive polymer includes poly (3,4-dioxyethylthiophene: polystyrene sulfonic acid) (PEDOT:PSS), poly (thiophene), poly (p-phenylene sulfide), polycarbazole, polyindole, polyaniline, polypyrrole, poly (fluorene), polyphenylene, polypyrene, polyazulene, polynaphthalene, polyacetylene, or poly (p-phenylene vinylene).

4. A hybrid electrolytic capacitor, characterized in that: include: an anode foil having a dielectric oxide film thereon; a cathode foil; a separator disposed between the anode foil and the cathode foil; a solid electrolyte formed on the surface of the dielectric oxide film on the anode foil, and the solid electrolyte includes a conductive polymer; as well as a liquid electrolyte filling the space between the anode foil, the cathode foil, and the separator, wherein the liquid electrolyte comprises a solvent having a boiling point higher than 150° C., The solid electrolyte, the liquid electrolyte, or both of them include a zwitterionic compound, the chemical structure of which is Where R 1 It is C 1-6 A straight or branched alkyl group; R 2 , R 3 , and R 4 Each is independently H or C 1-6 A straight or branched alkyl group; and L is C 1-12 A straight chain or branched alkylene group.

5. The hybrid electrolytic capacitor according to claim 4, characterized in that: When the solid electrolyte includes the zwitterionic compound, the zwitterionic compound accounts for 1 wt % to 50 wt % of the solid electrolyte.

6. The hybrid electrolytic capacitor according to claim 4, characterized in that: When the liquid electrolyte includes the zwitterionic compound, the zwitterionic compound accounts for 1 wt % to 50 wt % of the liquid electrolyte.

7. The hybrid electrolytic capacitor according to claim 4, characterized in that: When the solid electrolyte and the liquid electrolyte include the zwitterionic compound, the chemical structure of the zwitterionic compound in the solid electrolyte is the same as the chemical structure of the zwitterionic compound in the liquid electrolyte.

8. The hybrid electrolytic capacitor according to claim 4, characterized in that: When the solid electrolyte and the liquid electrolyte include the zwitterionic compound, the chemical structure of the zwitterionic compound in the solid electrolyte is different from the chemical structure of the zwitterionic compound in the liquid electrolyte.

9. The hybrid electrolytic capacitor according to claim 4, characterized in that: The solvent having a boiling point higher than 150° C. includes propylene glycol, glycerol, γ-butyrolactone, γ-valerolactone, N-methylpyrrolidone, dimethyl sulfoxide or sulfolane.

10. The hybrid electrolytic capacitor according to claim 4, characterized in that: The liquid electrolyte also includes a liquid polymer.

11. The hybrid electrolytic capacitor according to claim 10, wherein: The liquid polymer comprises polyalkylene glycol.